Validation of the Quasi-Two-Level Operation for a Flying Capacitor Converter in Medium-Voltage Applications - Stefan Christoph Mersche; Rüdiger Schwendemann; Marc Hiller (Energies, 2023)
Standard medium-voltage converters are operated at low switching frequencies using bulky passive components. One concept to change this involves the quasi-two-level operation (Q2O) of multilevel converters that use fast-switching semiconductors to minimize the need for passive components. The flying capacitor converter (FCC) uses SiC semiconductors and operates with Q2O to minimize passive components. In this paper, two different quasi-two-level algorithms are analyzed. A medium-voltage prototype was built and low-voltage and medium-voltage measurements were used to validate the concept. A particular focus is on the overvoltage, the <semantics>dv/dt</semantics> behavior of the converter, as well as the dynamic behavior.